1963
DOI: 10.1128/aem.11.5.436-445.1963
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection of Aerosolized Pathogenic Fungi on Laboratory Surfaces

Abstract: of aerosolized pathogenic fungi on laboratory surfaces. I. Tissue phase. Appl. Microbiol. 11:436-445. 1963.-The effect of several fungicides on laboratory surfaces contaminated with the tissue phase of aerosolized Blastomyces dermatitidis, Coccidioides immitis, Cryptococcus neoformans, and Histoplasma capsulatum was ascertained. A statistical analysis of the data shows the correlation between fungi, surfaces, time, and concentration of disinfectant. All fungicides were effective at established times and concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1970
1970
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…For all experiments except some preliminary work, we decided to use a 2 percent solution of Amphyl (a commercial product with a mild odor, which contains potassium ricinoleate, o-phenylphenol, p-tert-amylphenol, and alcohol, and is produced by Lehn & Fink Corporation). This compound, one of the widely used hospital and laboratory bactericides and fungicides, is similar to other phenolic compounds that have previously been shown, under controlled conditions, to be effective in killing pathogenic fuigi on various surfaces (14,15).…”
Section: Methods In Field and Laboratorymentioning
confidence: 81%
See 1 more Smart Citation
“…For all experiments except some preliminary work, we decided to use a 2 percent solution of Amphyl (a commercial product with a mild odor, which contains potassium ricinoleate, o-phenylphenol, p-tert-amylphenol, and alcohol, and is produced by Lehn & Fink Corporation). This compound, one of the widely used hospital and laboratory bactericides and fungicides, is similar to other phenolic compounds that have previously been shown, under controlled conditions, to be effective in killing pathogenic fuigi on various surfaces (14,15).…”
Section: Methods In Field and Laboratorymentioning
confidence: 81%
“…This disinfectant therefore seems to afford an effective and inexpensive method for the control of S. schenckn. Without doubt many other substances could be used effectively in controlling similar S. schenckii contaminations (14,15). It has been shown that a number of substances which preserve wood also have helped to prevent S. schenckii from growing on support timbers in South African mines (20).…”
Section: Undoubtedly Other Cases Of Sporotrichosis Wouldmentioning
confidence: 99%